Translingualism as an Open Educational Language Practice: Raising Critical Language Awareness on Facebook - Carl Blyth; Amanda Dalola (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
The term Open Educational Practice (OEP) is often defined as the process of creating and adapting OER. However, in the context of this study, we take OEP to include any practice that "opens up" a "closed" educational ecosystem by expanding learners' social networks and by increasing learners' participation and autonomy. Our study is framed in terms of one of the OER Research Hub's guiding hypotheses: "OER leads to critical reflection by educators, with evidence of improvement in their practice." In this case, the improved practice refers to how French-language educators sought to overcome prescriptivist attitudes linked to the "monolingual orientation" of traditional classroom instruction by adopting a translingual paradigm in keeping with recent research in applied linguistics (Cook, 1992, 1999; Blyth, 1995; MLA Report, 2007; Kramsch, 2010; Levine, 2011; Canagarajah, 2015). More precisely, we examine how language educators extended an OER titled Français interactif (Blyth, 2009, 2012; Kelton, Guilloteau & Blyth, 2011) by creating an accompanying Facebook page as an online "affinity space" (Gee, 2005) where traditionally proscribed practices such as code switching and lexical borrowing were not only accepted but encouraged. Following Canagarajah (2015), we understand translingual practice as an umbrella term referring to a language learner's integrated repertoire of communicative strategies based on multiple languages and modalities. We examine the social dynamics of various translingual practices that routinely occur on the Français interactif Facebook page and conclude by arguing that open, translingual affinity spaces provide an ideal place for raising learners' critical language awareness.